2018
DOI: 10.1096/fj.201800691r
|View full text |Cite
|
Sign up to set email alerts
|

Peptidylarginine deiminase 4: a nuclear button triggering neutrophil extracellular traps in inflammatory diseases and aging

Abstract: Peptidylarginine deiminase 4 (PAD4) is a nuclear citrullinating enzyme that is critically involved in the release of decondensed chromatin from neutrophils as neutrophil extracellular traps (NETs). NETs, together with fibrin, are implicated in host defense against pathogens; however, the formation of NETs (NETosis) has injurious effects that may outweigh their protective role. For example, PAD4 activity produces citrullinated neoantigens that promote autoimmune diseases, such as rheumatoid arthritis, to which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 143 publications
(212 reference statements)
1
106
0
2
Order By: Relevance
“…Interestingly, a similar EV-mediated export of deiminated histones, as observed in cow serum-EVs in the current study, was recently identified in the naked mole-rat, an animal with unusual immunological and metabolic traits [98], as well as in alligator, also an animal with unusual antimicrobial, including anti-viral responses [93]. Deiminated histone H3 is commonly used as an indicator for neutrophil extracellular trap formation (NETosis) [31,244], which has been related to PAD4 and implicated in anti-viral responses in cattle respiratory syncytial virus disease [42], in response to parasitic infections in cattle [245][246][247] as well as in response to certain antibiotics [248]. Interestingly, in crocodilians, extracellular histones H2A and H4 have been identified to act as inhibitors of viral (HIV) infection in vitro [249], although roles for post-translational deimination were not assessed.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, a similar EV-mediated export of deiminated histones, as observed in cow serum-EVs in the current study, was recently identified in the naked mole-rat, an animal with unusual immunological and metabolic traits [98], as well as in alligator, also an animal with unusual antimicrobial, including anti-viral responses [93]. Deiminated histone H3 is commonly used as an indicator for neutrophil extracellular trap formation (NETosis) [31,244], which has been related to PAD4 and implicated in anti-viral responses in cattle respiratory syncytial virus disease [42], in response to parasitic infections in cattle [245][246][247] as well as in response to certain antibiotics [248]. Interestingly, in crocodilians, extracellular histones H2A and H4 have been identified to act as inhibitors of viral (HIV) infection in vitro [249], although roles for post-translational deimination were not assessed.…”
Section: Discussionsupporting
confidence: 81%
“…Both neutrophil elastase (NE) and peptidyl arginine deiminiaseā€4 (PAD4) have been implicated in NET formation, 50ā€“53 although there is disagreement on the conditions and requirements for their involvement (for reviews, see [47, 48, 54]). PAD4 is extensively studied in the context of NET formation, where it mediates citrullination of histones, disrupts nucleosomes and allows chromatin unspooling and NET formation (for review see [55]). NE is also known to directly cleave extracellular ILā€1Ī² at tissue damage sites 56,57 although reports show this processing may actually inactivate the cytokine 58 .…”
Section: Resultsmentioning
confidence: 99%
“…Somewhat unexpectedly, Cit-H3 did not correlate well with the other two markers, but did associate strongly with platelet levels. It is believed that the predominant driver of histone citrullination (i.e., production of Cit-H3) in NETs is the enzyme peptidlyarginine deiminase 4 (PAD4) (38). However, neutrophils can be triggered to undergo NETosis by a variety of stimuli, and in vitro studies demonstrate that not all pathways to NETosis are equally reliant on PAD4 activity (39); for example, stimuli that lead to robust reactive oxygen species production may be relatively PAD4-independent (40).…”
Section: Discussionmentioning
confidence: 99%